CORCHIA, L., MÜLLER-DOOHM, S. und OUTHWAITE, W. (Hg.). Habermas global. Wirkungsgeschichte eines Werks. Berlin: Suhrkamp, 2019, 894 pp. - López de Lizaga, José Luis (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: CORCHIA, L., MÜLLER-DOOHM, S. und OUTHWAITE, W. (Hg.). Habermas global. Wirkungsgeschichte eines Werks. Berlin: Suhrkamp, 2019.